2006
DOI: 10.1149/1.2207821
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Saccharin Transformation to Metal Sulfides and Effect of Inclusions on Corrosion Susceptibility of Electroplated CoFe Magnetic Films

Abstract: The electroplated magnetic alloys ͑1.0T Ni 80 Fe 20 , 1.6T Ni 45 Fe 55 , 2.4T Co 40 Fe 60 ͒, obtained in the presence of saccharin, and sputtered magnetic alloys of the same composition showed dramatically different corrosion properties at pH 5.9. The higher corrosion susceptibility of electroplated magnetic alloys, known for many years, was generally attributed to sulfur inclusions into the deposit. However, there was no direct evidence of the structure of sulfur-containing molecules included in deposit. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 35 publications
1
61
1
2
Order By: Relevance
“…30 However, magnetic alloys prepared by electrodeposition in the presence of saccharin show very poor corrosion resistance due to sulfur-induced corrosion. 30 Many efforts are being made to find a non-saccharin additive which will improve corrosion properties. Unfortunately, some complexing organic non-saccharin additives in electrodeposition of TM alloys, caused more than 40% decrease of B s -value due to the incorporation of oxygen compounds into the deposit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 However, magnetic alloys prepared by electrodeposition in the presence of saccharin show very poor corrosion resistance due to sulfur-induced corrosion. 30 Many efforts are being made to find a non-saccharin additive which will improve corrosion properties. Unfortunately, some complexing organic non-saccharin additives in electrodeposition of TM alloys, caused more than 40% decrease of B s -value due to the incorporation of oxygen compounds into the deposit.…”
Section: Resultsmentioning
confidence: 99%
“…33 The effect of MA concentration on the saturation magnetization was examined using 400-500 nm thick CoFe films deposited on six inch round alumina coated AlTiC wafers using 100 nm Ru seed layers. The CoFe films deposited using a standard paddle configuration 30 with a 1000 Oe external magnetic field and pulse current densities of i on = 15 mA/cm 2 (t on = 2.5 s), i off = 0.0 mA/cm 2 (t off = 1.0 s). The uniformity of CoFe films, defined as Sigma/Mean thickness x 100, was optimized to ∼2% by changing the ratio of holder/wafer current densities.…”
Section: Methodsmentioning
confidence: 99%
“…The origin of oxygen is from organic compounds present in plating solution and from NiOH, Ni(OH) 2 and NiO, which are formed possibly through mechanism discussed in a our recent paper. 30 The total amount of light elements present as "impurities" is much higher in Ni (4.23 at. %) than in Ni 78 P 22 film (0.276 at.…”
Section: D240mentioning
confidence: 99%
“…Notably, we have found that the molecules of organic additives and their reduction products were incorporated into the deposit by dissolution of deposit and HPLC analysis of the obtained solution. 30,31 The origin of S, Cl, and B comes from anions present in electrolytes which are presumably complexed with Ni +2 ions forming neutral salts. The origin of oxygen is from organic compounds present in plating solution and from NiOH, Ni(OH) 2 and NiO, which are formed possibly through mechanism discussed in a our recent paper.…”
Section: D240mentioning
confidence: 99%
“…Additives and surfactants are widely employed in the electrochemical deposition practice for controlling the microstructure, resulting in grain refinement, causing leveling and brightening, and reducing internal stress [147,148]. Tabakovic et al report that examples of organic additives are saccharin and sodium lauryl sulfate (NaLS) [156].…”
Section: Electrochemical Deposition System and Processmentioning
confidence: 99%